Persepsi Generasi Z Terhadap Peran Pendidikan Hukum Dalam Membentuk Kesadaran Antikorupsi - Kayla Fellicia Putri; Leon Leon; Ayudia Aura Ancesar Putri Bakar; Subakdi Subakdi (Journal on Education, 2024)
This article discusses the perceptions of Generation Z regarding the role of legal education in shaping anti-corruption awareness. Generation Z, comprised of individuals born between the mid-1990s and early 2010s, is an integral part of a developing society. The role of legal education in shaping anti-corruption awareness becomes increasingly crucial in the context of a constantly changing and interconnected global environment through technology. The article analyzes Generation Z's perceptions of legal education and how legal education can be utilized as a tool to build anti-corruption awareness among them. Through literature review and interviews with various members of Generation Z, the article explores efforts that can be undertaken by educational institutions, governments, and society to enhance the effectiveness of legal education in combating corruption. The findings of this article provide valuable insights into how legal education can be optimally utilized to create a generation more conscious of the importance of integrity and honesty in social and governmental structures.